A design framework for technology prioritisation in the context of through-life engineering services - Chi, Jie; Latsou, Christina; Erkoyuncu, John Ahmet; Grenyer, Alex; Rushton, Keith R.; Brocklebank, Simon (Elsevier, 2021)
Lack of methods on standardising the prioritisation of technologies within the context of Through-life Engineering Services (TES) has been identified. Inspired by the TES value streams and support activity assets, existing within a common TES framework, a new design framework for technologies prioritisation is proposed. A dynamic toolkit to identify the most suitable technology is also developed, using a Quality Function Deployment method, Analytic Hierarchy Process and ROI analysis. A real case study from the defence sector is employed to validate the developed design framework and toolkit; the results show a well-structured guide that can effectively simplify the decision-making process.
Keywords: TES framework; dynamic toolkit; technology prioritisation method; design framework; Through-life Engineering Services